SYARAT CUKUP SUATU OPERATOR LINEAR A SEBAGAI GENERATOR DARI FUNGSI KOSINUS COS - Tri Widjajanti (FMIPA Universitas Papua, 2008)
In this paper, it is discussed an operator A as generator of cosine function Cos by determine the sufficient conditions for operator A as generator of cosine function Cos.